2004
DOI: 10.1007/s00038-004-3041-y
|View full text |Cite
|
Sign up to set email alerts
|

Disability trends in gender and race groups of early retirement ages in the USA

Abstract: Americans aged 65-69 years manifest a significant improvement in health over the 1980s-1990s but the dynamics differs in gender and race groups. Possible reasons for these differences are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Crimmins (2004) argues the most severe physical disability is an inability to provide self-care and is measured by activities of daily living (ADL) including: bathing or showering, dressing, eating, getting in or out of bed or chairs, walking, and using the toilet. Examining five waves of the National Long Term Care Survey from 1982 to 1999, Arbeev et al (2004) found the highest ADL disability prevalence among black women age 70 and higher (22 to 27 percent) followed by white women (16 to 18 percent). ADL disability prevalence for black and white men was significantly lower, 16 to 23 percent and 10 to 13 percent, respectively.…”
Section: Disparities In Chronic Diseases Impairments and Disabilitymentioning
confidence: 99%
“…Crimmins (2004) argues the most severe physical disability is an inability to provide self-care and is measured by activities of daily living (ADL) including: bathing or showering, dressing, eating, getting in or out of bed or chairs, walking, and using the toilet. Examining five waves of the National Long Term Care Survey from 1982 to 1999, Arbeev et al (2004) found the highest ADL disability prevalence among black women age 70 and higher (22 to 27 percent) followed by white women (16 to 18 percent). ADL disability prevalence for black and white men was significantly lower, 16 to 23 percent and 10 to 13 percent, respectively.…”
Section: Disparities In Chronic Diseases Impairments and Disabilitymentioning
confidence: 99%
“…Many demographic and epidemiological studies explore the effects of chronological age, race/ethnicity, and sex on mortality rates and susceptibility to chronic disease [ 1 5 ], but it remains an open research question whether race/ethnicity and sex affect molecular markers of aging directly. To what extent clinical biomarkers of inflammation, dyslipidemia, and immune senescence relate to cellular markers of aging also remains an open question.…”
Section: Introductionmentioning
confidence: 99%
“…Despite multiple public health efforts, racial disparities in health outcomes persist . African Americans are more likely to have higher rates of physical disability than Caucasians . In a study of high‐functioning elderly women, African Americans who were preclinically disabled were more likely to be disabled 18 months later as compared to their Caucasian counterparts .…”
mentioning
confidence: 99%
“…1 African Americans are more likely to have higher rates of physical disability than Caucasians. 2,3 In a study of high-functioning elderly women, African Americans who were preclinically disabled were more likely to be disabled 18 months later as compared to their Caucasian counterparts. 4 Socioeconomic status (SES) may explain these differences, as several studies have suggested, although other studies have shown that differences persist after adjustment for SES.…”
mentioning
confidence: 99%